Digitalization: Innovation in public services (Case Study Implementation of the Complaints Service Unit in Surakarta (ULAS) and Klaten Regency Industry and Manpower Office) - Seta, Heka Jalu; Suharto, Didik Gunawan; Setyowati, Kristina (Journal of Government and Civil Society, 2024)
This study examines the impact of digital transformation on public service innovation through a comparative analysis of the Surakarta Complaints Service Unit (ULAS) and the Industry and Manpower Office in Klaten Regency. As digitalization becomes a cornerstone of modern governance, it offers critical pathways to enhancing efficiency, responsiveness, and transparency within public administration. By investigating digitalized complaint management and service processes, this research highlights how digital platforms can streamline responses to community needs and foster improved administrative practices. Through a qualitative approach, utilizing both literature review and in-depth interviews, findings reveal that digitalization not only addresses public grievances effectively but also plays a vital role in establishing principles of good governance. This study underscores the significance of digital transformation in elevating public sector responsiveness and accountability, providing valuable insights for other regions aiming to leverage technology in public service reforms.Penelitian ini mengkaji dampak transformasi digital terhadap inovasi layanan publik melalui analisis komparatif pada Unit Layanan Aduan Surakarta (ULAS) dan Dinas Perindustrian dan Tenaga Kerja Kabupaten Klaten. Digitalisasi telah menjadi landasan dalam tata kelola modern, menawarkan jalur penting untuk meningkatkan efisiensi, responsivitas, dan transparansi dalam administrasi publik. Dengan meneliti manajemen pengaduan dan proses layanan yang terdigitalisasi, penelitian ini menyoroti bagaimana platform digital dapat menyederhanakan respons terhadap kebutuhan masyarakat dan mendorong praktik administratif yang lebih baik. Melalui pendekatan kualitatif, menggunakan tinjauan pustaka dan wawancara mendalam, temuan menunjukkan bahwa digitalisasi tidak hanya secara efektif menangani keluhan publik tetapi juga berperan penting dalam penerapan prinsip tata kelola yang baik. Studi ini menegaskan pentingnya transformasi digital dalam meningkatkan responsivitas dan akuntabilitas sektor publik, serta memberikan wawasan berharga bagi daerah lain yang ingin memanfaatkan teknologi dalam reformasi layanan publik.